Answer:
The sum of the given expression is (m+1).
Step-by-step explanation:
The given expression is
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)[/tex]
Use distributive property to to simplify the given expression.
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)=\frac{1}{3}(9)+\frac{1}{3}(-6m)+\frac{1}{4}(12m)+\frac{1}{4}(-8)[/tex]
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)=3-2m+3m-2[/tex]
Add like terms.
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)=(3-2)+(-2m+3m)[/tex]
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)=(1)+(m)[/tex]
[tex]\frac{1}{3}(9-6m)+\frac{1}{4}(12m-8)=m+1[/tex]
The sum of the given expression is (m+1).